SIMULATION MODELLING POSSIBILITIES IN TEACHING ECONOMIC PROCESSES - Grabusts, Pēteris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
For the purpose of simulation models visualization of various economic disciplines, it is appropriate to use specialized programs that allow to characterize the nature of a particular model, but also make it possible to carry out a simulation model based on various parameters. This article substantiates the usefulness of introduction the simulation models at the initial research process, when simulation models can be imported parallel with analytical relations acquisition. Series of research were carried out in order to demonstrate the suitability of the Matlab Simulink for the purpose of visualization of various simulation models of various economic disciplines. Often, the analytical solution is much simpler than the visual Simulink model, but in the perspective of training purposes, it gives an understanding of the usefulness of such models. In the research part of the study the modelling capabilities in economic studies were demonstrated- adapted models in optimal tax rates computing and equilibrium determination in the competitive market.